Mitotic recombination between homologous chromosomes generates H-2 somatic cell variants in vitro. - Potter, T A (1987)
A spontaneously arising variant clone that does not express the H-2Dd and H-2Ld molecules was isolated by immunoselection from an (H-2b X H-2d)F1 cell line. This variant clone expresses H-2Kb, H-2Db, and H-2Kd molecules. Southern blot analysis demonstrated that the variant was heterozygous at the H-2K, I, and S loci but had lost the H-2Dd and H-2Ld genes. Karyotype analysis showed that neither of the chromosome 17s in the variant had undergone detectable deletions. Quantitative Southern blot analysis demonstrated that the variant had two copies of the H-2Db gene, whereas the parental cell line had one copy of H-2Db. The loss of the H-2Ld and H-2Dd genes, accompanied by the attainment of homozygosity at H-2Db, is consistent with a recombination between the two chromosome 17 homologues. We conclude that although mitotic recombination between homologues has been difficult to demonstrate, it may not be infrequent and may account for the development of mutant genotypes in somatic cells in vitro. Such a mechanism occurring in vivo could result in the emergence of cells that are homozygous for deleterious alleles even though the individual may be constitutionally heterozygous.